Understanding resilience among transition-age youth with serious mental illness: protocol for a scoping review. Issue 9 (19th September 2022) - Nesbitt, Amy E; Sabiston, Catherine M; deJonge, Melissa L; Barbic, Skye Pamela; Kozloff, Nicole; Nalder, Emily Joan
Abstract : Introduction: Transition-age youth (16–29 years old) are disproportionately affected by the onset, impact and burden of serious mental illness (SMI; for example, depression, bipolar disorder, schizophrenia spectrum disorders). Emerging evidence has increasingly highlighted the concept of resilience in mental health promotion and treatment approaches for this population. A comprehensive synthesis of existing evidence is needed to enhance conceptual clarity in this area, identify knowledge gaps, and inform future research and practice. As such, the present scoping review is guided by the following questions: How has resilience been conceptualised and operationalised in the transition-age youth mental health literature? What factors influence resilience among transition-age youth with SMI, and what outcomes have been studied within the context of transition-age youth's mental health recovery? Methods and analysis: The present protocol will follow six key stages, in accordance with Arksey and O'Malley's (2005) established scoping review methodology and recent iterations of this framework, and has been registered with Open Science Framework (https://osf.io/rzfc5 ). The protocol and review process will be carried out by a multidisciplinary team in consultation with community stakeholders. A comprehensive search strategy will be conducted across multiple electronic databases to identify relevant empirical literature. Included sources will address the population of transition-age youth (16–29 years) diagnosed with SMI, the concept of resilience (in any context) and will report original research written in English. Data screening and extraction will be completed by at least two independent reviewers. Following meta-narrative review and qualitative content analyses, findings will be synthesised as a descriptive overview with tabular and graphical summaries. Ethics and dissemination: University of Toronto Health Sciences Research Ethics Board approval was obtained to complete the community stakeholder consultation stage of this review. Results will be disseminated through conference presentations, publications, and user-friendly reports and graphics.